Gatekeepers as Care Providers: The Care Work of Patient‐centered Medical Home Clerical Staff. (28th March 2016) - Solimeo, Samantha L.; Ono, Sarah S.; Stewart, Kenda R.; Lampman, Michelle A.; Rosenthal, Gary E.; Stewart, Greg L.
Abstract : International implementation of the patient‐centered medical home (PCMH) model for delivering primary care has dramatically increased in the last decade. A majority of research on PCMH's impact has emphasized the care provided by clinically trained staff. In this article, we report our ethnographic analysis of data collected from Department of Veterans Affairs staff implementing PACT, the VA version of PCMH. Teams were trained to use within‐team delegation, largely accomplished through attention to clinical licensure, to differentiate staff in providing efficient, patient‐centered care. In doing so, PACT may reinforce a clinically defined culture of care that countermands PCMH ideals. Such competing rubrics for care are brought into relief through a focus on the care work performed by clerks. Ethnographic analysis identifies clerks' care as a kind of emotional dirty work, signaling important areas for future anthropological study of the relationships among patient‐centered care, stigma, and clinical authority.